2014
DOI: 10.9734/bmrj/2014/12487
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Fungi: A Poor Candidate for the Production of Lovastatin

Abstract: Aim:The aim of the present study was to screen soil and endophytic fungi for production of lovastatin. Methodology: Soil fungi were isolated by dilution plating technique and endophytic fungi from selected medicinal plants by using standard procedures. All isolates were tested for lovastatin production by Solid State Fermentation (SSF) using wheat bran as substrate. Results: The soil isolate, Aspergillus terreus NCBI (KM017963) showed positive for lovastatin (1.0 mg/G DWS) whereas none of the endophytic fungi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 16 publications
(7 reference statements)
2
16
0
Order By: Relevance
“…On the other hand, the soil isolate Aspergillus terreus (AH007774.1) showed perfect homology to lovastatin DNA sequences with 100% identity with lovastatin gene cluster sequence (55328/55328) (Table 1, Figure 1). These results are in perfect agreement with our previously published results [4] on the lack of lovastatin production by endophytic fungi and suggest that, the lack of lovastatin production may be due to the absence of lovastatin encoding DNA sequences.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…On the other hand, the soil isolate Aspergillus terreus (AH007774.1) showed perfect homology to lovastatin DNA sequences with 100% identity with lovastatin gene cluster sequence (55328/55328) (Table 1, Figure 1). These results are in perfect agreement with our previously published results [4] on the lack of lovastatin production by endophytic fungi and suggest that, the lack of lovastatin production may be due to the absence of lovastatin encoding DNA sequences.…”
Section: Resultssupporting
confidence: 93%
“…The lovastatin gene cluster includes 18 genes that are involved in lovastatin biosynthetic pathway and, of which LovE and LovF encode for transcriptional regulatory factor and diketide synthase (DKS), respectively [3,14]. Further studies with the endophytic fungi at the molecular level will categorically confirm our previous biochemical [4] and the present bioinformatic study.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…We have previously demonstrated that endophytic fungi as poor producers of lovastatin since none of the 54 endophytic fungi isolated by us from medicinal plants produced any detectable level of lovastatin even after 10 days of incubation [9]. Also, it was noticed that Aspergillus terreus, an endophyte, did not produce lovastatin while a soil isolate of the same fungus produced significant levels of lovastatin under identical growth conditions [8]. Since not much information is available on lovastatin production by endophytic fungi, this study was designed to analyze and compare the genetic makeup of lovastatin producing Aspergillus terreus (KM017963), a soil isolate, with selected endophytic fungi of medicinal plants.…”
Section: Resultsmentioning
confidence: 85%